Effects of long-term nitrogen addition on the δ15N and δ13C of Larix gmelinii and soil in a boreal forest - Guancheng Liu; Zhiwei Yin; Guoyong Yan; Shuang Liu; Xiaochun Wang; Yajuan Xing; Qinggui Wang (Ecological Processes, 2022)
Abstract Background Natural abundance of carbon (C) and nitrogen (N) stable isotope ratios (δ13C and δ15N) has been used to indicate the state and cycle of ecosystem C and N. However, it is still unclear how C and N cycle of boreal forests respond to the N deposition. Results We conducted an 8-year continuous N addition field experiment in a Larix gmelinii forest in Greater Khingan Mountains, Northeast China. Four N treatments (0, 25, 50, 75 kg N ha−1 year−1) were built. The effects of N addition on the δ13C and δ15N of needle, branch, bark, and fine root of Larix gmelinii and soil were studied. The result of the balance between the N input and output flux showed that N addition significantly increased the δ15N in each organ of Larix gmelinii, but did not change the δ15N of soil. We also found that the N absorption by needles of Larix gmelinii could increase the needle photosynthesis rate and δ13C by increasing carboxylation, but N addition had no significant effect on the δ13C of soil and other organs. In addition, both the soil δ15N and δ13C increased with the soil depth. Conclusions Long-term N addition may lead to more open C and N cycles and further affect plant nutrient acquisition strategies in boreal forest ecosystems.